Influence of Visiting Lecturer's Quality on Indonesian-Malaysian Student Perceptions - Yulianita, Neni; Yuniati, Yenni; Tresnawiwitan; Susilawati, Eka; Maulana, Faisal; Firjatullah Irvanianto, Raihan (Mediator: Jurnal Komunikasi, 2024)
This article highlights the importance of a lecturer's success when providing a learning process to their students. For this reason, the study of the success of the learning process needs to be researched by looking at the influence of learning quality on student perceptions. The Faculty of Communication Sciences of Universitas Islam Bandung (UNISBA) has conducted a series of Online Visiting Lecturers in collaboration with the Faculty of Leadership and Management (FKP), Universiti Sains Islam Malaysia (USIM). The study opted comparative quantitative research approach to investigate the influence of teaching quality on Indonesian-Malaysian Students’ Persception  among the students who have participated in the visiting lecturer program. Based on the results of the calculation of R-square and R-value, the teaching quality positive influences the perception of Indonesian student by 54,3% and that of Malaysian student by 73.7%. It demonstrated that the teaching quality of the visiting lecturer program positively influences the perceptions of Indonesian-Malaysian students.